2004
DOI: 10.1055/s-2004-824821
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Language Assessment for African American English-Speaking Children: A Historical Perspective

Abstract: The diagnostic problem of how validly to assess the language of children who speak dialects different from Mainstream American English (MAE) has challenged the field of communication disorders for several decades. The key to its solution is to recognize differences due to dialect or development and remove them from the initial diagnosis of a disorder. A new approach to the puzzle, implemented jointly by University of Massachusetts scholars and the Psychological Corporation (TPC), takes two directions: (1) it p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…As Figure 3 shows, the noncontrastive features distinguish the typically developing from languageimpaired children, but they are an even better diagnostic for MAE background children than for children who speak with strong difference from MAE (Figure 4). This is consistent with the observation made by Seymour 11 in the introduction to this issue that normal AAE features can appear similar to patterns of language disorder in MAE speakers. The linguistic pattern of an African American child (or a child from another racial or ethnic background) who has a language disorder and comes from a home and community where MAE is the dominant dialectal pattern will mimic those of an AAE speaker.…”
Section: Dialect Identification Versus Risk Evaluation/ciolli Seymoursupporting
confidence: 92%
“…As Figure 3 shows, the noncontrastive features distinguish the typically developing from languageimpaired children, but they are an even better diagnostic for MAE background children than for children who speak with strong difference from MAE (Figure 4). This is consistent with the observation made by Seymour 11 in the introduction to this issue that normal AAE features can appear similar to patterns of language disorder in MAE speakers. The linguistic pattern of an African American child (or a child from another racial or ethnic background) who has a language disorder and comes from a home and community where MAE is the dominant dialectal pattern will mimic those of an AAE speaker.…”
Section: Dialect Identification Versus Risk Evaluation/ciolli Seymoursupporting
confidence: 92%
“…The composite picture painted by the DELV-NR and the LS profiles included restricted vocabulary, lower than average sentence complexity, and ineffective pragmatics-that is, difficulties generating cohesive narratives or poor understanding of the listener's needs. Seymour (2004) suggested that using a combination of noncontrastive morphosyntax (e.g., past tense copula, which is not optional in AAE, as found in Part 2 of the DELV-ST) and other linguistic structures was effective for diagnosis of CLD AAEfirst learners. The DELV-NR added information about comprehension of long-distance movement in complex sentences, articles, question asking, and fast mapping, among other constructions.…”
Section: The Phenotype Of LImentioning
confidence: 99%
“…Taylor (1969) was among the first to articulate this view within the field of communication disorders, and it was subsequently highlighted in a special issue of Language, Speech, and Hearing Services in Schools (Taylor, 1972) on "Language and the Black Urban Child." This perspective has been kept in the forefront by researcher-activists such as Craig and Washington (2006), Seymour (2004;Seymour, Bland, & Green, 1998;Seymour & Seymour, 1979), and Stockman (1986Stockman ( , 1996Stockman ( , 2010, among many others. The caution has been reiterated in strong position statements from the American Speech-LanguageHearing Association (1983,2003), which reaffirm that differences based on cultural dialects are not to be considered a basis for referral to speech or language services.…”
mentioning
confidence: 99%
“…The contrastive/noncontrastive model 1 described in Seymour 2 was applied in the development of a dialect-sensitive phonology assessment. As with other domains of language, contrastive refers to phonological features that differ (contrast) between African American English (AAE) and Mainstream American English (MAE).…”
Section: Phonology Domainmentioning
confidence: 99%